Giant edge state splitting at atomically precise graphene zigzag edges - Shiyong Wang (Nature Portfolio, 2016)
The zigzag edges of graphene host edge-localized electronic states with aligned electron spins, but these states strongly interact with metallic substrates. Here, the authors measure the electronic structure of graphene nanoribbons after transferring them to an insulating support.